2002
DOI: 10.1086/344099
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Precise Measurement of Matter Clustering: Lyα Forest Data at Redshifts 2–4

Abstract: We measure the filling factor, correlation function, and power spectrum of transmitted flux in a large sample of Lyα forest spectra, comprised of 30 Keck HIRES spectra and 23 Keck LRIS spectra. We infer the linear matter power spectrum P (k) from the flux power spectrum P F (k), using an improved version of the method of Croft et al. (1998) that accounts for the influence of redshift-space distortions, non-linearity, and thermal broadening on the shape of P F (k). The evolution of the shape and amplitude of P … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

51
631
4
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 428 publications
(688 citation statements)
references
References 104 publications
(148 reference statements)
51
631
4
2
Order By: Relevance
“…A model with somewhat less small-scale power, such as the lower amplitude LCDM model favored by recent Lya forest studies (McDonald et al 2000 ;Croft et al 2001), might fare better in this regard, perhaps matching the observed DLA abundance with a closer to the v c,min expected photoionization value. We are unable to make predictions for total absorption in the TCDM model with our current simulations because the paucity of structure above our resolution threshold makes our extrapolation procedure unreliable.…”
Section: Absorption In L Ow-mass Halosmentioning
confidence: 91%
“…A model with somewhat less small-scale power, such as the lower amplitude LCDM model favored by recent Lya forest studies (McDonald et al 2000 ;Croft et al 2001), might fare better in this regard, perhaps matching the observed DLA abundance with a closer to the v c,min expected photoionization value. We are unable to make predictions for total absorption in the TCDM model with our current simulations because the paucity of structure above our resolution threshold makes our extrapolation procedure unreliable.…”
Section: Absorption In L Ow-mass Halosmentioning
confidence: 91%
“…n s In Figure 2, we compare the prediction of our models for the matter power spectrum with data extracted from galaxy catalogs (e.g., Two-Degree Field Galaxy Redshift Survey [2dFGRS]; Percival et al 2001;Verde et al 2002;Peacock et al 2001) or the Lya forest (Gnedin & Hamilton 2002;Croft et al 2002). In view of the uncertainties from bias and nonlinearities, the agreement is good for all models (A-D).…”
mentioning
confidence: 82%
“…The 2dFGRS (Percival et al 2001;Peacock et al 2001;Verde et al 2002) and Lya (Gnedin & Hamilton 2002;Croft et al 2002) data have been evolved to , although we have not convolved our theoretical data with z p 0 the experimental window functions. The galaxy power spectrum has a bias compared to theoretical predictions that is not included in the figure. energy T into potential energy V, effectively "stopping" the field.…”
mentioning
confidence: 99%
“…However, even after marginalizing over these parameters there is enough information in the clustering statistics of the flux F to constrain the shape and amplitude of the matter power spectrum (e.g., Croft et al 2002;McDonald et al 2006). Lyα forest surveys conducted for BAO allow high precision measurements of flux correlations on smaller scales, so they have the statistical power to achieve tight constraints on matter clustering.…”
Section: The Lyα Forest As a Probe Of Structure Growthmentioning
confidence: 99%